Intergenerational Changes Microevolution or Long-Term Adaptational Fluctuations – Facts and Views - Wolański, Napoleon (Anthropological Review, 1987)
The literature data and own results, presented in this analysis, seem to indicate that: Intergenerational changes in contemporary man are, not unidirectional and exhibit fluctuations. These changes are directly (environmental factors) or indirectly (external selecting factors) caused by the ecological and social conditions, therefore they are of an adaptational nature. Secular changes in body size, proportions and components, as well as their physiological and motor consequences in contemporary man are mainly caused by abundant nutrition (excess of calories) and a sedentary mode of life, although the selection factor seems to modifie some effects of the above factors, it is definitely less effective and its contribution to the overall processes is much smaller. The rate of progressive development becomes accelerated beginning from infancy and till completion of adolescence, whereas the reproductin period is prolonged and menopause is shifted to a late age, ageing is retarded. This is probably due to better nutrition, shortening of the duration of diseases, improvement of living conditions, and changes in the intensity of stress factors.